Students’ Perception on Flipped Learning Conducted in an Online Writing Class During the Pandemic: A Survey Research - Yulitriana; Olga Dona Retsi; Eriani; Indrini Oktamelinae; Yogi Atma Pratama (The Study Program of English Education of Palangka Raya University, 2022)
Flipped learning (FL) is the approach used in this research based on two reasons: firstly, the traditional learning fails to facilitate students’ need for knowledge construction, collaboration, and sufficient practice and feedback in online learning; therefore, the teacher had to use another approach called Flipped Learning. Secondly, Flipped Learning has the potency to facilitate the students’ needs mentioned earlier. This research is a survey research and was conducted in an online Writing Class at the university of Palangka Raya and a questionnaire and interview were the instruments used to collect the data needed. The result shows that the success in implementing the FL could be achieved when the four pillars of FL integrated appropriately in the teaching and learning process. As the result, the students gave highly positive responses towards FL that it can facilitate their needs in the online writing class during the pandemic as the four pillars are accordingly implemented; therefore, the pre-learning activities, practices, small group discussions and feedbacks are adequately provided through FL.